2004
DOI: 10.1093/ps/83.7.1148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Mannan Oligosaccharide, Bacitracin Methylene Disalicylate, or Both on the Live Performance and Intestinal Microbiology of Turkeys

Abstract: Hybrid male turkeys were fed to 18 wk of age in a completely randomized design with 10 replicate pens (18 birds each) per treatment to compare growth promoters. Four dietary treatments were used: negative control (CON), bacitracin methylene disalicyate (BMD) at 55 mg/kg to 6 wk and 27.5 mg/kg thereafter, mannan oligosaccharide (MOS) at 0.1% to 6 wk and 0.05% thereafter, and BMD and MOS at concentrations listed above. There were 3 toms/m2 (3.59 ft2/tom) on fresh pine shavings inoculated with used litter. A 6-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2
20

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 16 publications
6
84
2
20
Order By: Relevance
“…From 22 to 42 days of age and in the whole period, feed intake was not (P>0.05) infl uenced by any treatments. Similarly, SIMS et al (2004), GODOI et al (2008) and SOUZA et al (2008 reported no difference in broilers' feed intake at 42 days of age attributed to the use of MOS or antibiotics. However, ESONU et al (2004), while studying the inclusion of cellulose enzyme in poultry feed over the period of 28 and 35 days of age, saw an increase in feed intake and decrease in weight gain due to the inclusion of the enzyme.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…From 22 to 42 days of age and in the whole period, feed intake was not (P>0.05) infl uenced by any treatments. Similarly, SIMS et al (2004), GODOI et al (2008) and SOUZA et al (2008 reported no difference in broilers' feed intake at 42 days of age attributed to the use of MOS or antibiotics. However, ESONU et al (2004), while studying the inclusion of cellulose enzyme in poultry feed over the period of 28 and 35 days of age, saw an increase in feed intake and decrease in weight gain due to the inclusion of the enzyme.…”
Section: Resultsmentioning
confidence: 93%
“…Mannan oligosaccharides (MOS) derived from the yeast cell wall have high binding affi nity, providing a competitive binding site for oligosaccharide-specifi c bacteria. The benefi ts of MOS are based on properties that include changes in the intestinal fl ora, a reduction in mucosa turnover rate, and the modulation of the immune system in the intestinal lumen (SIMS et al, 2004). Therefore, this study aimed to evaluate the use of β-mannanase and mannan oligosaccharides (MOS) to replace growth promoters in broiler diets.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2003) found a dose-dependent effect of FOS on ADG in broilers; whereas, Juskiewicz et al (2006) reported no impact on the performance or productivity of turkeys. However, on MOS supplementation, Sims et al (2004) reported an improvement in live weight in turkeys. Piray et al (2007) reported that relative weight of breast and thigh to body weight were significantly (p<0.01) higher in Fermacto ® (Aspergillus oryzae meal) fed broilers as compared to control.…”
Section: Introductionmentioning
confidence: 94%
“…(IMMERSEEL et al, 2004) e das características anatômicas do trato gastrintestinal, promovendo o aumento da superfície de absorção da mucosa intestinal, podendo provocar melhoria no desempenho animal. (COSTA et al, 2008;IBRAHIM, 2011;OLIVEIRA et al, 2009;SIMS et al, 2004) Além do desempenho, estudos relatam que o uso de prebiótico pode melhorar a qualidade dos ovos, principalmente a casca, pois quando o prebiótico alcança o intestino grosso ele é fermentado e convertido em ácido graxo de cadeia curta, diminuindo o pH luminal, solubilizando o cálcio e favorecendo sua absorção, consequentemente melhorando a qualidade da casca. (KRUGER et al, 2003;OLIVEIRA et al, 2009;YOUSEFI & KARKOODI, 2007) Um prebiótico que tem sido muito estudado e utilizado é a parede celular de Saccharomyces cerevisiae, produto da extração do conteúdo celular da levedura e rica num oligossacarídeo a base de alfa-manose e beta-glucose (KOGAN & KOCHER, 2007), o mananoligossacarídeo (MOS).…”
Section: Discussionunclassified